Expansion takes an expression from factored form and uses the distributive property to remove the brackets and write the expression as a sum of products. Such as $\left(a+2\right)\left(b+3\right)=ab+3a+2b+6$(a+2)(b+3)=ab+3a+2b+6.

The distributive property: $A\left(B+C\right)=AB+AC$A(B+C)=AB+AC

You can reduce this working to one line by remembering the first term multiplies each in the second bracket, then the second term multiplies each in the second bracket.

Hence, $\left(x+5\right)\left(x+2\right)=x^2+2x+5x+10$(x+5)(x+2)=x2+2x+5x+10. Which we could then simplify to $x^2+7x+10$x2+7x+10.

Remember

After expanding check if the expression can be simplified by collecting like-terms.